2021
DOI: 10.1088/1742-6596/2090/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Bearing friction effect on cup anemometer performance modelling

Abstract: In the present work, the effect of the friction forces at bearings on cup anemometer performance is studied. The study is based on the classical analytical approach to cup anemometer performance (2-cup model), used in the analysis by Schrenk (1929) and Wyngaard (1981). The friction torque dependence on temperature was modelled using exponential functions fitted to the experimental results from RISØ report #1348 by Pedersen (2003). Results indicate a logical poorer performance (in terms of a lower rotation spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The rotor was coupled to the body of a First Class Vector Instruments A100L2 anemometer, whose characteristics are described in Table 2 . Additionally, a heater was attached to the body of the cup anemometer to prevent loss of performance due to low atmospheric temperatures at high altitude levels over the ground [ 39 ]. Figure 2 shows the cup anemometer composed of the designed rotor, the Vector Instruments A100L2 sensor body, and the heater attached to the latter.…”
Section: Methodsmentioning
confidence: 99%
“…The rotor was coupled to the body of a First Class Vector Instruments A100L2 anemometer, whose characteristics are described in Table 2 . Additionally, a heater was attached to the body of the cup anemometer to prevent loss of performance due to low atmospheric temperatures at high altitude levels over the ground [ 39 ]. Figure 2 shows the cup anemometer composed of the designed rotor, the Vector Instruments A100L2 sensor body, and the heater attached to the latter.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it can be concluded that there is a large uncertainty in terms of the calibration of an anemometer for air velocity measurements at very low-density conditions. Since the aerodynamic torque, QA, depends linearly on the dynamic pres reasonable to assume that the relationship between this variable and the torque by the friction forces, Qf, will be a determining parameter in the performances o mometer at least when faced with small variations in this relationship [11]. If th ature of the cup anemometer bearings is constant, it can be assumed that th torque is constant, although as expressed in Equation ( 2), this frictional torque pends (to a lesser extent [11]) on the rotational speed.…”
Section: Effect Of Air Density Variations On Cup Anemometers Performa...mentioning
confidence: 99%
“…Since the aerodynamic torque, QA, depends linearly on the dynamic pres reasonable to assume that the relationship between this variable and the torque by the friction forces, Qf, will be a determining parameter in the performances o mometer at least when faced with small variations in this relationship [11]. If th ature of the cup anemometer bearings is constant, it can be assumed that th torque is constant, although as expressed in Equation ( 2), this frictional torque pends (to a lesser extent [11]) on the rotational speed. Thus, in the absence of experimental studies, a preliminary hypothesis suggests that, for very low air Since the aerodynamic torque, Q A , depends linearly on the dynamic pressure, it is reasonable to assume that the relationship between this variable and the torque produced by the friction forces, Q f , will be a determining parameter in the performances of the anemometer at least when faced with small variations in this relationship [11].…”
Section: Effect Of Air Density Variations On Cup Anemometers Performa...mentioning
confidence: 99%
See 2 more Smart Citations